2018
DOI: 10.1021/acsami.7b15759
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Characteristics of Intercellular Calcium Wave Communication in Micropatterned Assemblies of Single Cells

Abstract: Micropatterned substrates offer a unique possibility to define and control spatial organization of biological cells at the microscale, which greatly facilitates investigations of the cell-to-cell communication in vitro. Here, we developed a simple micropatterning strategy to resolve various spatiotemporal characteristics of intercellular calcium wave (ICW) communication among isolated BV-2 microglial cells. By using a single-ring assembly, we found that the direction of the initial transmitter secretion was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…Thus, the most likely reason is intercellular communication by secreted chemical messenger molecules. Indeed, it is known that cells may secrete ATP upon stimulation, [ 31a,35 ] which acts as a paracrine transmitter of intercellular Ca 2+ waves to excite increased [Ca 2+ ] i in other cells, [ 36 ] which has been also demonstrated here in the above described control experiments, cf. Figures S22 and S23, Supporting Information.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Thus, the most likely reason is intercellular communication by secreted chemical messenger molecules. Indeed, it is known that cells may secrete ATP upon stimulation, [ 31a,35 ] which acts as a paracrine transmitter of intercellular Ca 2+ waves to excite increased [Ca 2+ ] i in other cells, [ 36 ] which has been also demonstrated here in the above described control experiments, cf. Figures S22 and S23, Supporting Information.…”
Section: Resultssupporting
confidence: 66%
“…This can be attributed to the diffusion of released free Ca 2+ , or Ca 2+ induced Ca 2+ release [ 30 ] in other part of the cell, or mixed effects. The decay of [Ca 2+ ] i of a stimulated cell to its baseline has been reported to happen within 1 min, [ 31 ] which was much slower in our results. Of note, the photobleaching effect under continuous imaging can be ignored by using the LSM880 set‐up due to its low excitation power (Table S1, Supporting Information).…”
Section: Resultssupporting
confidence: 40%
See 1 more Smart Citation
“…Studies have shown calcium and ATP acting in a range of different communication pathways, including injury response and intercellular communication 89 94 . Calcium waves in particular have been shown to act as communicators for damage and regeneration 93 , 95 97 , suggesting these as potential candidates for inter-embryo signaling mechanisms for CEMA. We made use of a loss-of-function reagent known to block ATP signaling via the P2X/P2Y receptors: the purinergic receptor type 2 antagonist suramin 98 101 to see whether it would prevent the CEMA effect and render large groups as susceptible to defects as small ones 93 , 94 , 102 .…”
Section: Resultsmentioning
confidence: 99%
“…Fabrication of Micropatterned Substrate: Micropatterned substrates were prepared as previously described. [48] In brief, glass substrates (𝜑 = 25 mm) were immersed in chromic acid lotion for thorough cleaning and then dried at 80 °C for 20 min. Afterward, they were put into a vacuum desiccator containing hexamethyldisilazane (HMDS, Sigma, USA) for vapor phase deposition for at least 30 min.…”
Section: Methodsmentioning
confidence: 99%